A life in letters - Rogelja, Nataša (Dve domovini, 2019)
This article follows a circular path. Its starting point is the well-preserved family ar-chive of more than a hundred letters written by Sr. Conradina to her family back home in Slovenia from her assigned mission in India. It then journeys through layers of historical context important for understanding the qualitative methodological approaches, reflecting on various aspects relevant to the analysis of the letters (material aspects, questions of comprehension, content issues, the ethnographic context, etc.). Finally, it reaches - or rather comes back to - the source, the missionary herself, writing letters from India to Slovenia from within the framework of different hierarchies, discourses and relationships.
Keywords: India; Indija; letters; life writing; migracije; migrations; misijoni; missions; pisma; Resnik, Konradina; Slovenian women missionaries; slovenske misijonarke; women; ženske; življenjske zgodbe